Effect of nitrogen and phosphorus levels on white rust disease of mustard [Brassica juncea (L.) Czern and Coss.]: EFFECT OF NITROGEN AND PHOSPHORUS LEVELS ON WHITE RUST DISEASE OF MUSTARD - A N CHAUBEY; VIRENDRA SINGH; SATYBHAN SINGH; R D SHUKLA; HETRAM (Journal of Oilseeds Research, 2019)
India is one of the largest oilseed economies of the world. The contribution of oilseeds to the agricultural economy of India ranks second only to food grains. An experiment was conducted to evaluate the judicious use of fertilizers against white rust disease in mustard. Susceptible plant variety JKMS-8001 was sown in 2 m x 3 m plot size with recommended spacing in a randomized block design with three replications and nine treatments viz., T1 - (Control), T2 - (80 N+40 P2O5 kg/ha), T3 - (100 N +40 P2O5 kg/ha), T4 -(120 N+40 P2O5 kg/ha), T5 - (140 N+40 P2O5 kg/ha), T6 - (100 N+30 P2O5 kg/ha), T7 - (100 N +50 P2O5 kg/ha), T8 - (100 N+60 P2O5 kg/ha) and T9 - (100 N +70 P2O5 kg/ha). Minimum percent disease incidence (17.03) and maximum percent disease control (67.66) were observed in treatment in T9 (100 kg N +70 kg P2O5 /ha). Furthermore, maximum yield and yield attributes were found in T9 (100 kg N +70 kg P2O5 /h).